An exposition of Iqbal’s ideas on human nature and personality - Abdul Razak, Mohd Abbas; Ismail, Nik Ahmad Hisham (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2013)
Early ideas on human nature and personality were presented by Muslim scholars during the Golden Age of Islam (750-1258). The decline of the Islamic civilization and the dawn of the era of European colonization has somehow dwindled the study on man and his personality until the poet-philosopher Mohammed Iqbal (1879-1938) came up with his philosophy on the Ego (Khudi). Using philosophy and poetry as his vehicles, Iqbal called upon the Muslims to pay attention to the development and maintenance of the human Ego. Given Iqbal‟s fame in the East and West, it is pertinent to explore his ideas on human nature, philosophy of Ego or self, and personality. This study surveys the underlying factors that challenged Iqbal to conceptualize a theory on personality which is very different from others in the Islamic world.